PENGGUNAAN MEDIA WORLD WALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS IV SD NEGERI 13 TANJUNG BONAI AUR KECAMATAN SUMPUR KUDUS KABUPATEN SIJUNJUNG - Rosi Yusnita (Adiba Aisha Amira, 2024)
This research aims to improve student learning outcomes in Islamic Religious Education (PAI) subjects using Wordwall-based interactive learning media for class IV students at SD Negeri 13 Tanjung Bonai Aur, Sumpur Kudus District, Sijunjung Regency. This research uses the Classroom Action Research (PTK) method which consists of two cycles. Each cycle involves the stages of planning, implementation, observation, and reflection. The research results showed an increase in student learning outcomes from cycle I to cycle II. In cycle I, the average student score was 77 with a classical completion level of 50%. After implementing Wordwall media in cycle II, the average student score increased to 86 with a classical completion level of 90%. In addition, students' responses to the use of Wordwall media were very positive, which was reflected in their increased enthusiasm and activeness in learning. This research concludes that the use of Wordwall media is effective in improving student learning outcomes in PAI subjects. It is hoped that this media can be widely applied to create more interesting and interactive learning.